LOCAL COMMUNITY INVOLVEMENT IN TOURISM DEVELOPMENT OF KERINCI REGENCY, JAMBI PROVINCE - Ahlunnaza Pandu Rahardjo; Desiana Desiana (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2021)
The involvement of local communities are one of the efforts that can make development in tourist destinations that are allegedly in accordance with the needs of the community. Kerinci Regency included in one of the eighty eight National Tourism Strategic Areas (KSPN). The purpose of this study is to identify potential tourist destinations, forms of community involvement, factors that influence community involvement, and the influence of tourist visits on community involvement. This study uses qualitative research method, data analysis techniques starting from data reduction, data presentation, and drawing conclusions. The actor-network analysis presented in this study to understand how the phenomenon of tourism occurs. The result of this research is that the phenomenon of tourism occurs continuously, each who comes to visit and then gives input, making the potential that there will increase. The level of participation of traders and tour guides are at the first level, namely Spontaneous Participation. Then, the level of participation of homestay managers, small boat tenants, drivers, performing arts providers, parking attendants, and ticket attendants are at the Induced Participation level. The factor of traditional leader is the main factor that must be considered, besides economic, cultural, and forest factors. These factors work by strengthening and weakening relationships that have existed before. Tourist visits have an influence on the variation of homestays, variation in pattern of tourist movements, the emergence of trainings, packages and tourist programs, the development of customary rules, strengthening with local resources (Cinnamon), and increasing the number of homestays